Conclusion: exciting conclusion chapter! / Asmah Alia Mohamad Bohari - Mohamad Bohari, Asmah Alia (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
The Centre of Studies in Art & Design, Architecture, Planning, and Surveying is thrilled to contribute to Universiti Teknologi MARA's outstanding aspiration of being the Globally Renowned University by 2025. International Outbound Mobility to West Kalimantan in 2023 was the first step. with many more. The programme culminated with a trip to the Malaysian Consulate in Pontianak to discuss prospects for future cooperation in West Kalimantan. This programme has increased UiTM's international visibility and helped faculty and students grow by exchanging ideas and forging new relationships with peers from the neighbouring country. The Kapuas River Cruise is the extra touch that helps us fit in with the community and leaves an imprint on everyone. How can we forget every smile and laughter we had during the whole trip? Everyone concludes the programme with a great smile and lasting memories.